The Influence of Student Self-Confidence and Discipline on Learning Achievement in Social Sciences Subjects for Class VIII Student at SMP Negeri 7 Pematangsiantar Academic Year 2023/2024. - Sihombing, Sifra Oktaviana; Sihombing, Sotarduga; Siahaan, Anton Luvi (Journal of Educational Analytics, 2024)
Student self-confidence and discipline are very important factors for improving student learning achievement. This type of research is quantitative descriptive research, with a population of all students in grades VIII-4 to VIII-8 at SMP Negeri 7 Pematangsiantar totaling 160 students and a research sample of 115 students selected using random sampling techniques. Data collection techniques are carried out by observation and distributing questionnaires, while data analysis techniques use validity tests, reliability tests, normality tests, normal distribution tests, multiple linear regression tests, t tests, f tests and coefficient of determination tests. Based on the results of data analysis using Excel, there is a joint or simultaneous influence between students' self-confidence and discipline on learning achievement, seen from the Fcount value of 45.816 > Ftable value of 3.077, with a contribution from the x to y variables of 44.9%.